PELAYANAN PUBLIK BERBASIS ELEKTRONIK DAN PERILAKU ANTI KORUPSI - Manurung, Elsa Debora; Rahmayani Sembiring, Shafira Nadya; Sulistyani, Wanodyo (Faculty of Law, Parahyangan Catholic University, 2019)
Advancement in the information and communication technology make possible the development of e-government. The Indonesian government already grasped the opportunity to develop its own e-government system in providing public services. The obvious intent is to increase the quality of public service provision by the bureaucracy. This is hoped to be achieved by securing transparency and accountability of public officials. It is also to be expected that e-governance will be able to eradicate or at least decrease the possibility of corruptive behaviour. Unfortunately, fact speaks differently. Cases to be analysed here are: corruption committed by public officials working at the Investment and One Stop Service Office of the Bandung Municipality and those performed by public officials managing e-procurement services. In particular, this article shall discuss the issue how to develop e-government as to better at eradicating and preventing corruption by public officials.